Molecular dynamics modeling of the radial heat transfer from silicon nanowires - Bejenari, Igor; Burenkov, Alexander; Pichler, Peter; Deretzis, Ioannis; La Magna, Antonino (International Conference on Simulation of Semiconductor Processes and Devices, SISPAD, 2020)
Thermal transport in radial direction in Si nanowires embedded into amorphous silicon dioxide has been studied using nonequilibrium molecular dynamics simulations. For comparison, we also considered the axial heat transfer. For Si nanowires with a radius of 2.6 nm, both radial and axial thermal conductivities were found to be about independent of the SiO2 thickness ranging from 1 nm to 3 nm. The radial thermal conductivity of the Si core and of the covering SiO2 material are similar and nearly equal to 1 W⊙K-1m-1. Thermal resistances for the heat transfer from uniformly heated nanowires in radial direction are by a factor of 3 to 4 lower than those for the heat transfer in axial direction.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Heat transport; Molecular Dynamics (MD); Nanowire; Thermal conductivity